Implementation of Policy for Controlling and Licensing of Street Vendors in the City of Palembang - Dandi Irawan Subandara; Doris Febriyanti; Isabella Isabella (Publica: Jurnal Pemikiran Administrasi Negara, 2022)
This study aimed to determine how to implement controlling and licensing street vendors at Musi 6 Bridge, Seberang Ulu I District, Palembang City. The research method used in this research is qualitative. The analysis results and findings in the field are (1) optimal Standards and Policy Targets. (2) Policy Performance. This indicator has been running well, as seen from the performance of policy implementers who work optimally. (3) Resources, this indicator is optimal, as seen from the budget, human resources, facilities and infrastructure. (4) Inter-Agency Communication The implementation of this indicator has been going well. This can be seen from the coordination meetings held regularly. (5) The characteristics of the Implementing Agency for this indicator have been running well. The division of tasks and authorities is in accordance with the SOP and conducting evaluations at the end of each month. (6) Social, Economic and Political Environment, these indicators have been running well. (7) Attitude of the Implementer This indicator of the attitude of the implementer has gone well because the attitude of the implementer is firm. So it can be concluded that the implementation of the Policy on Control and Licensing of Street Vendors at Musi 6 Bridge has been running well and optimally. The researcher's suggestions for this research are expected to the Government to always make appeals and outreach to the public about government regulations prohibiting selling on the side of the road or the sidewalk.